2016
DOI: 10.1111/jjns.12115
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life and psychological well‐being in men with benign prostatic hyperplasia: An integrative review

Abstract: This review highlights the need to conduct further study on health-related quality of life and the psychological well-being of patients with benign prostatic hyperplasia, especially in an Asian context. Such efforts promote patient-centric care and improve patient satisfaction through incorporating the concept of health-related quality of life into clinical practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
0
18
0
2
Order By: Relevance
“…Symptoms of BPH, unlike other chronic diseases such as hypertension and diabetes, are often perceived as less serious. Some may simply consider it an inconvenience in daily life, while others do not think treatment is necessary and that the condition it will naturally improve [ 41 ]. We can judge that as delay occurs in the treatment of BPH for this reason, the patient’s subjective health state lowers and HRQOL consequently reduces.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of BPH, unlike other chronic diseases such as hypertension and diabetes, are often perceived as less serious. Some may simply consider it an inconvenience in daily life, while others do not think treatment is necessary and that the condition it will naturally improve [ 41 ]. We can judge that as delay occurs in the treatment of BPH for this reason, the patient’s subjective health state lowers and HRQOL consequently reduces.…”
Section: Discussionmentioning
confidence: 99%
“…However, the health-related quality of life of BPH patients is considered as poor, and their psychological well-being is severely affected. For instance, postvoid residual urine, lower urinary tract symptoms, anxiety and depression are identified to be significant predictive factors of the health-related quality of life of patients with enlarged prostate (10) . Thus, we suggested that men with enlarged prostate may not wear during 6 months something on the body that is helpless.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a "placebo" or "sham" group as a control could provide more statistical rigor with respect to results. However, most men with CP/CPPS have psychological problems, they largely do not respond to medical interventions, and pain syndrome is associated with a decrease in QoL [46,47]. Similar problems are observed in men with BPH suffering from depression and anxiety, their health-related QoL is considered poor, and their psychological well-being is seriously affected [48,49].…”
Section: Discussionmentioning
confidence: 95%